Privacy preserving approach based on proximity privacy for numerical sensitive attributes - Jing XIE; Jian-pei ZHANG; Jing YANG; Bing ZHANG (Tongxin xuebao)
A model based on proximity breach for numerical sensitive attributes is proposed.At first，it divides numerical sensitive value into several intervals on the premise of protecting the internal relations between quasi-identifier attributes and numerical sensitive attributes.Secondly，it proposes a (k，ε)-proximity privacy preserving principle to defense proximity privacy.In the end，a maximal neighborhood first algorithm (MNF) is designed to realize the (k，ε)-proximity.The experiment results show that the proposed model can preserve privacy of sensitive data well meanwhile it can also keep a high data utility and protect the internal relations.